Sozaboy a novel in rotten English - Saro-Wiwa, Ken 1941-1995 (Longman African writers, 1996)
"Sozaboy describes the fortunes of a young naive recruit in the Nigerian Civil War: from the first proud days of recruitment to the disillusionment, confusion and horror that follows. The author's use of 'rotten English'--a mixture of Nigerian pidgin English, broken English and idiomatic English--makes this a unique and powerful novel"--Back cover